2007
DOI: 10.1063/1.2720184
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of strength, elongation, and toughness on grain size in metallic structural materials

Abstract: The dependence of yield strength, uniform elongation, and toughness on grain size in metallic structural materials was discussed. The toughness is defined as the product of yield strength and uniform elongation. The yield strength versus grain size can be well described by the Hall-Petch relation; however, the uniform elongation versus grain size is not well understood yet. A simple model involving the densities of geometrically necessary dislocations and statistically stored dislocations was proposed to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…For annealed material with polygonal grains, the basic Hall–Petch equation relating yield stress is expressed as: σ=σ0+kyD1/2 where σ 0 is the intrinsic strength of matrix phase due to various strengthening mechanisms, D is the effective grain size, k y (MPa · mm 1/2 ) is a constant pre‐factor, varying significantly with alloy contents and processing history . The fitted parameter σ 0 = 40 MPa is consistent with the earlier reports on ferritic steels, while the k y = 14 MPa mm 1/2 in the present work is lower than the value, that is, 20.5 MPa mm 1/2 reported earlier . The increase in k y for ferritic steels might be caused by the high defect density in the effective size of grains.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For annealed material with polygonal grains, the basic Hall–Petch equation relating yield stress is expressed as: σ=σ0+kyD1/2 where σ 0 is the intrinsic strength of matrix phase due to various strengthening mechanisms, D is the effective grain size, k y (MPa · mm 1/2 ) is a constant pre‐factor, varying significantly with alloy contents and processing history . The fitted parameter σ 0 = 40 MPa is consistent with the earlier reports on ferritic steels, while the k y = 14 MPa mm 1/2 in the present work is lower than the value, that is, 20.5 MPa mm 1/2 reported earlier . The increase in k y for ferritic steels might be caused by the high defect density in the effective size of grains.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is reasonable to exert that the comparison of tensile properties among the annealing conditions will be unaffected by the choice of sample size. Recently, Galindo‐Nava et al proposed a new model to elaborate the correlation between strength and microstructure of steels. In their model, it was assumed that the increment in strengthening caused by the solid solution and dislocations was of the order of 5–10 MPa due to the clean matrix phase with recrystallized ferritic grains.…”
Section: Discussionmentioning
confidence: 99%
“…indicates that STS 316L parts with nearly full density can be produced by HIP process at both 1130 ℃ and 1200 ℃. lower elongation [22,23]. These characteristics were confirmed by the tensile tests results listed in Table 5.…”
Section: Mechanical Propertiessupporting
confidence: 75%
“…The results showed that grain size, grain orientation and grain boundaries can be changed using SLHS. Most of important mechanical properties of metals such as yield stress, ductility and hardness can be changed by changing these 31 32 . So by changing the grain shape (size, orientation and boundaries) some changes are expected in final mechanical properties during laser melting.…”
Section: Discussionmentioning
confidence: 99%